Vichada meteorite impact effects from simulation of regional environmental consequences of a meteoroid impact on Earth (2018)
This study estimates the regional environmental consequences of the impactor extraterrestrial body that could produce the probable Vichada impact crater structure on the Vichada Plain, in Colombia, South America. This paper details the parameter assumptions upon which the estimation is made. It describes an approach to quantifying the principal impact processes that could have affected the landscape in the vicinity of the probable Vichada impact event in the past. The key parameters are impactor diameter, impactor density, impact velocity before atmospheric entry, impact angle, and the distance from the impact at which the environmental effects are to be calculated, and the target type of sedimentary rock or crystalline rock. These parameters were chosen with support from The Vichada Structure dimensions obtained from remote sensing data interpretation, regional geologic mapping and interpreted satellite data and ground-based gravity and magnetic anomalies. The calculations are based on compiled novel algorithms for estimating the thermal radiation emitted by the impact-generated vapor plume or fireball, and the intensity of seismic shaking. Model validation is performed by obtaining the approximates various dimensions of the Vichada impact crater and ejecta deposit, as well as estimating the severity of the air blasting both crater-forming and air burst impacts. We illustrate the utility of the calculations by examining the predicted environmental consequences in seven localities of the Colombian territory, through hypothetical impact scenarios occurring in Cumaribo and Puerto Carreño (Vichada), Puerto Inirida (Guainía), Puerto Gaitán and Villavicencio (Meta), Mitú (Vaupes) and Bogotá, D.C. It is concluded that the most wide-reaching environmental consequence is seismic shaking. Both ejecta deposit thickness and air-blast pressure decay much more rapidly with distance than with seismic ground motion. Close to the impact site, the most devastating effect is from thermal radiation; however, the curvature of the Earth implies that distant localities are shielded from direct thermal radiation because the fireball is below the horizon. These results would guide further detailed fieldwork hunting for direct impact crater evidence and interpret high-resolution geophysical studies and borehole that could be carried out in the probable Vichada impact crater area shortly.